Language as supervernaculars: A case study on language and online gaming - de Silva, D.G.N.T. (University of Colombo, 2017)
Supervernaculars emerge as semiotic codes which form a sociolinguistic system as a result of the processes of globalization in a technologically-driven world. This very creation of supervernaculars challenges the traditional notion of speech community of early sociolinguists, where language functioned within a particular territory, adhering to the norms and rules of a given community. With the emergence of supervernaculars, the concept of speech community is challenged with the formation of de-territorialized and trans-idiomatic communities on the virtual platform. The current study engages in an analysis of the language used in online gaming to emphasize the ways in which language functions as a supervernacular on a virtual platform. The paper provides multiple case studies which illustrate how the English language functions as a Supervernacular. In doing so, it presents a form of English that actually occurs in use, which deviates from the imagined standard of English. A purposive sampling method was used for data collection, and the data was analysed using thematic analysis. Cyber ethnography has been employed as the primary method of data collection. Findings suggest that, on the virtual platform, supergroups are created through the sharing of linguistic resources irrespective of cultural, social, and geographical backgrounds. In addition, world Englishes, rather than the imagined standard of English, function as supervernaculars, thus highlighting the role of dialects of languages. This leads to the formation of super speech communities in segments of the virtual platform, such as in the instance of online gaming, where individuals across the globe,irrespective of boundaries, use the global language of English as a supervernacular for communication and social interaction.
Keywords: supervernaculars, speech communities, globalization, online gaming